2012
DOI: 10.1097/brs.0b013e3182740e56
|View full text |Cite
|
Sign up to set email alerts
|

Pedicle Screw Design and Cement Augmentation in Osteoporotic Vertebrae

Abstract: Polymethylmethacrylate cement augmentation clearly enhances pedicle screw fixation in osteoporotic vertebrae when tested in pure pullout. The technique used for cement injection and choice of specialty screws can have a significant impact on the magnitude of this effect. Fenestrated screws have the capacity to confine cement placement in the vertebral body and may provide enhanced safety from cement extrusion into the spinal canal. It is feasible to inject high-viscosity PMMA through this fenestration geometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(36 citation statements)
references
References 33 publications
1
32
0
1
Order By: Relevance
“…One of the limits of these augmented screws was related to a high risk of cement leakage associated with a nonacceptable neurologic risk. Recent developments of partially fenestrated screws are one the solutions to these risks as it allows a cement injection in the first anterior third of the screw, increasing the pull-out strength with a decreased risk of leakage [9] (Figure 3). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the limits of these augmented screws was related to a high risk of cement leakage associated with a nonacceptable neurologic risk. Recent developments of partially fenestrated screws are one the solutions to these risks as it allows a cement injection in the first anterior third of the screw, increasing the pull-out strength with a decreased risk of leakage [9] (Figure 3). …”
Section: Discussionmentioning
confidence: 99%
“…In every case, fixation of the fracture was done using a posterior percutaneous transpedicular instrumentation using cement-augmented cannulated fenestrated screws (Longitude, Medtronic, or Mantis, Stryker). Screws used in this study were partially cannulated fenestrated screws that allow injection of the cement in the first third of the screw when compared to fully cannulated fenestrated screws [9]. Pedicle screws were systematically inserted under anteroposterior and lateral fluoroscopic guidance.…”
Section: Methodsmentioning
confidence: 99%
“…Choma et al showed torque limits of augmented pedicle screws between 1.2 and 1.8 Nm in osteoporotic vertebrae. None of the tested vertebral bodies sustained failure of the cement-bone interface (Choma et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies demonstrate that PMMA augmentation can increase the screws' pull out strength in osteoporotic and normal vertebrae [18].…”
Section: Discussionmentioning
confidence: 99%